IMPLEMENTATION OF CONTINUOUS MIDWIFERY CARE ASSISTANCE IN PREGNANCY, LABOR, POSTPARTUM, NEWBORN, AND FAMILY PLANNING SERVICES - Nur Azizah Nur Azizah; Wiwik Muhidayati Wiwik Muhidayati; Nina Purnamasari Nina Purnamasari (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Pregnancy and birth are normal events in life. Excessive weight gain during pregnancy, at risk of causing pre-eclampsia, can also cause miscarriages and diabetic militus. The purpose of this study was to carry out ongoing obstetric care which included Third Trimester pregnancy, childbirth, postpartum, newborns and postpartum family planning.method uses documentation of the SOAP method. The subjects of this study were pregnant women in the third trimester, followed by childbirth, postpartum until the mother could decide on the method of birth control, and in the newborn. Data collection was carried out with anamnesa, physical examination, supporting examination, then analyzed according to the diagnosis of midwifery care. The results of the study showed that pregnancy care was given focus on pregnancy with more weight and physiological end result of pregnancy. At the first stage of childbirth care was obtained regarding the problem of anxiety that continued in the second stage due to the effective implementation. So that the end result of labor is known that the mother is in physiological labor. Postpartum care from 6 hours to 2 weeks, the mother is in physiological postpartum and the mother has decided the method of contraception. In the handling of newborns there is no gap, counseling provided by midwives by including family members so that neonatal care from 1 hour to 2 weeks the baby's condition looks healthy. Implementation of ongoing midwifery care must be maintained in order to improve the level of maternal and child health services.